Ferroptosis and Autophagy-Related Genes in the Pathogenesis of Ischemic Cardiomyopathy - Zheng, Yue; Gao, Wenqing; Zhang, Qiang; Cheng, Xian; Liu, Yanwu; Qi, Zhenchang; Li, Tong (Frontiers in Cardiovascular Medicine, 2022)
Background Obesity plays an important role in type 2 diabetes mellitus (T2DM) and myocardial infarction (MI). Ferroptosis and ferritinophagy are related to metabolic pathways, such as fatty acid metabolism and mitochondrial respiration. We aimed to investigate the ferroptosis- and autophagy-related differentially expressed genes (DEGs) that might be potential targets for MI progression. Methods GSE116250 was analyzed to obtain DEGs. A Venn diagram was used to obtain the overlapping ferroptosis- and autophagy-related DEGs. The enrichment pathway analysis was performed and the hub genes were obtained. Pivotal miRNAs, transcription factors, and drugs with the hub genes interactions were also predicted. The MI mice model was constructed, and qPCR analysis and single-cell sequencing were used to validate the hub genes. Results Utilizing the limma package and the Venn diagram, 26 ferroptosis-related and 29 autophagy-related DEGs were obtained. The list of ferroptosis-related DEGs was analyzed, which were involved in the cellular response to a toxic substance, cellular oxidant detoxification, and the IL-17 signaling pathway. The list of autophagy-related DEGs was involved in the regulation of autophagy, the regulation of JAK-STAT signaling pathway, and the regulation of MAPK cascade. In the protein-protein interaction network, the hub DEGs, such as IL-6, PTGS2, JUN, NQO1, NOS3, LEPR, NAMPT, CDKN2A, CDKN1A, and Snai1, were obtained. After validation using qPCR analysis in the MI mice model and single-cell sequencing, the 10 hub genes can be the potential targets for MI deterioration. Conclusion The screened hub genes, IL-6, PTGS2, JUN, NQO1, NOS3, LEPR, NAMPT, CDKN2A, CDKN1A, and Snai1, may be therapeutic targets for patients with MI and may prevent adverse cardiovascular events.